How do you solve, 3x-11y=9; -9x-33y=18. If there is no solution, why?

Follow
  • Follow publicly
  • Follow privately
  • Unfollow
Best Answer
The first equation is 3x-11y=9 and the second equation is;

3x+11y=-6 (you divide the equation by -3)

so

3x-11y=9
3x+11y=-6

6x=3
x=1/2

and 3/2-11y=9 3/2-9=11y y=-0.6816
  • Rate
  • Comment

Other Answers (5)

Rated Highest
  • Rated Highest
  • Oldest
  • Newest
  • Peter answered 4 years ago
    The second equation is NOT a multiple of the first one. If instead of an 18 there was a 27, ok, but that is not the case.
    And there are not infinite multiple solutions, just one, as outlined in marckd2002's answer which is correct. There are different ways to get to it, but I find this method to be the simplest.
    This is called the substitution method.
    The method of substitution involves five steps:

    Step 1: Solve for y in equation (1).
    Step 2: Substitute this value for y in equation (2). This will change equation (2) to an equation with just one variable, x.
    Step 3: Solve for x in the translated equation (2).
    Step 4: Substitute this value of x in the y equation you obtained in Step 1.
    Step 5: Check your answers by substituting the values of x and y in each of the original equations. If, after the substitution, the left side of the equation equals the right side of the equation, you know that your answers are correct.

    There are other methods you can use, they are:

    Elimination,
    Matrices,
    Graphing.

    For a detailed explanation on how to use them, you can visit:
    http://www.sosmath.com/soe/SE2001/SE2001...

    Source(s):

    This same question.
    School
    • Rate
    • Comment
  • Ozz123 answered 4 years ago
    3x-11y=9
    -9x-33y= 18

    multiply the first equation by 3 so you get
    9x-33y=27

    So the two equations look like this:
    9x-33y=27
    -9x-33y= 18
    Add those to up, then you'll get
    -66y=45
    y= -15/22

    Add the y in one of those equations let say number 2:
    -9x-(33*-15/22)=18
    -9x+22.5=18
    -9x=-4.5
    x=0.5
    • Rate
    • Comment
  • _TIM_ answered 4 years ago
    {
    3x - 11y = 9 (1)
    -9x - 33y = 18 (2)

    (1) <=> 9x - 33y = 18

    (1) # (2) => vô nghiệm
    • Rate
    • Comment
  • marckd2002 answered 4 years ago
    You need to take a facto away

    3x - 11y = 9
    3x = 11y + 9
    x = (11y + 9) / 3

    then you substitute the x in the other variable

    -9(11y + 9)/3 -33y = 18
    -33y - 27 -33y = 18
    -66y = 18 + 27
    y = -15/22

    and then change y for the number

    3x -11 (-15/22) = 9
    3x +15/2 = 9
    3x = 3/2
    x= 1/2
    • Rate
    • Comment
  • D.W. answered 4 years ago
    The second equation is a multiple of the first. Since you don't have two independent equations, you can't find a unique solution. There are infinitely many solutions.
    • Rate
    • Comment
  • Sign In 

    to add your answer

Who is following this question?

    %
    BEST ANSWERS
    Member Since:
    Points: Points: Level
    Total Answers:
    Points this week:
    Follow
     
    Unfollow
     
    Block
     
    Unblock